2019
DOI: 10.1007/s12975-019-00698-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease Increases Cerebral Microbleeds in Mouse and Man

Abstract: Brain microbleeds are increased in chronic kidney disease (CKD) and their presence increases risk of cognitive decline and stroke. We examined the interaction between CKD and brain microhemorrhages (the neuropathological substrate of microbleeds) in mouse and cell culture models and studied progression of microbleed burden on serial brain imaging from humans. Mouse studies: Two CKD models were investigated: adenine-induced tubulointerstitial nephritis and surgical 5/6 nephrectomy. Cell culture studies: bEnd.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 47 publications
5
86
0
3
Order By: Relevance
“…It is known that chronic kidney disease and hemodialysis are associated with a high incidence of microbleeds [21,22]. The underlying physiological mechanisms including increased permeability of the blood-brain barrier secondary to a high concentration of uremic toxins [21]. Indeed, the group of patients with COVID-19 diagnosed with CIAM have shown a more severe kidney failure in agreement with this new assumption.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It is known that chronic kidney disease and hemodialysis are associated with a high incidence of microbleeds [21,22]. The underlying physiological mechanisms including increased permeability of the blood-brain barrier secondary to a high concentration of uremic toxins [21]. Indeed, the group of patients with COVID-19 diagnosed with CIAM have shown a more severe kidney failure in agreement with this new assumption.…”
Section: Discussionmentioning
confidence: 72%
“…The third new hypothesis was formulated based on our results: the role of kidney failure, which was more severe in the group with CIAM. It is known that chronic kidney disease and hemodialysis are associated with a high incidence of microbleeds [21,22]. The underlying physiological mechanisms including increased permeability of the blood-brain barrier secondary to a high concentration of uremic toxins [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that mild CKD may lead to activation of limbic system, central sympathetic, stress-and pain-related brain areas (31). Some CKD-related neurological complications have been attributed to impaired permeability of the blood-brain barrier (22,32,33), neuroinflammation, and oxidative stress (21)(22)(23). Neurotoxicity induced by numerous substances, such as urea, accumulated in blood during kidney disease (34)(35)(36) might also play a role (33).…”
Section: Discussionmentioning
confidence: 99%
“…19 Mechanism for CMB includes uremia induced alteration in actin cytoskeleton and claudin-5 expression, a tight junction protein in endothelial cells. 20 Impaired renal function, age, and hypertension were all found to be associated with CMB in patients with ischemic stroke. 21 In a meta-analysis of studies involving recent ischemic stroke, documented AF and long term anti-coagulation therapy, future odds of ICH were noted to be associated with the presence of CMB at baseline (odds ratio [OR], 2.68; 95% CI, 1.19 to 6.01; P=0.017) and the number of CMB (OR for ICH, 5.5; 95% CI, 2.07 to 14.66; P=0.001 with CMB ≥5).…”
Section: Pathophysiology Of Af and Cva In Esrdmentioning
confidence: 99%
“…Cerebral microbleed (CMB), focal deposits of hemosiderin, is another pathophysiological aspect, which is associated with an increased risk of intracerebral hemorrhage (ICH), ischemic and hemorrhagic stroke, and is quite common among HD patients (54%) [ 19 ]. Mechanism for CMB includes uremia induced alteration in actin cytoskeleton and claudin-5 expression, a tight junction protein in endothelial cells [ 20 ]. Impaired renal function, age, and hypertension were all found to be associated with CMB in patients with ischemic stroke [ 21 ].…”
Section: Pathophysiology Of Af and Cva In Esrdmentioning
confidence: 99%